Perception Of Student Teachers on Integrated Teacher Education Programme at Senior Secondary Level - Sujata B Hanchinalkar; T.V. Somashekar; Praveen Kumar S., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2025)
Indian system of teacher education has been revamped after implementation of National Council for Teacher Education (NCTE) Regulation, 2014. The pre-service teacher education programme has been designed to develop professional competencies of student teachers. Therefore, NCTE regulation prescribed various forms of integrated approaches in teacher preparation at elementary level and secondary level. Much before NCTEs implementation of Integrated Teacher Education Programme (ITEP), Regional Institutes of Education (RIEs) had planned and successfully implemented the ITEP in Science, Social Science from last four decades. Since a decade, RIE Mysuru has also implemented ITEP [‘Master of Science Education’ (i.e. M.Sc.Ed.)] for teacher preparation at Senior Secondary, level which is one of its kind in the country. Therefore, the present study has been taken up to explore the perceptions of student teachers on Integrated Teacher Education Programme at Senior Secondary level at RIE Mysuru. The study reveals positive opinion of student teachers towards the Integrated Teacher Education Programme at Senior Secondary level. It also involved in preparation of large number of competent teachers for senior secondary level in meeting the needs of the present-day schools.
Keywords: Integrated Teacher Education Programme; Teacher Education; Senior Secondary level